Analisis Rencana Elektronifikasi Keuangan Daerah dalam Memperluas Kontribusi Zakat dengan Pendekatan Fishbone Diagram Analysis - Oktoviana Banda Saputri; Nurul Huda; Mulawarman Hannase (Department of Islamic Economics, IPB University, 2022)
This study aims to identify the root cause in planning of the implementation digital transformation of local government financial transactions to expand the role of zakat. This study modify the element of zakat as an instrument in regional fiscal financial policy. Government policies that impose restrictions on social interaction among the spread of the Covid-19 outbreak have convinced people to switch to the trend of digital transactions. The electronification activity for each transaction is one of the government's strategies in achieving the financial inclusion level target in 2024 of 90%. This study used a qualitative descriptive analysis using the Fishbone Diagram Analysis method with the 4M approach, there are Method, Manpower, Material, and Machine. Based on the analysis and mapping of the problems, it is concluded that there are still areas that need to be strengthened the plan of the regional government financial transaction electronification program in expanding the contribution of zakat, there are in the areas of government’s policy and regulation, human resources, infrastructure as well as synergy and coordination.